Nurses use of Pediatric early warning score in the public emergency ward - Knudsen, Tina C.; Helgesen, Ann Karin (Nordisk Tidsskrift for Helseforskning, 2024)
Background: Children are among the largest patient groups assessed in the public emergency ward. Early recognition of deterioration in health status is more complex in children than in adults. There is limited research on the use of Pediatric Early Warning Scores (Pevs) in the public emergency ward. Purpose: To assess nurses' experiences with the use of Pevs in public emergency ward. Results: The results indicate that Pevs is a useful tool in assessing sick children in emergency care. Pevs contributes to systematic assessment, standardization, continuity, and early identification of deterioration in children. Pevs can complement clinical observations and assessments, but nurses must also use clinical judgment and knowledge to capture changes not reflected in Pevs scores. The results also show that the majority of nurses desire more training, and that physicians should be included in the training. Conclusion: Pevs is a valuable tool, and there is a need for more training in its use to ensure effective collaboration and enhance patient safety.
Keywords: Pediatric Early Warning Score; Public emergency ward; Pediatric; PEWS